Giving Psychoeducation “Divorce on Family Perspective” to Main Potential University Psychology Students - Linda Sitepu; Aqmarina Husna (JUDIMAS, 2022)
Divorce is the end of a marriage. Divorce is the severance of the relationship between husband and wife, caused by the failure of the husband or wife in carrying out the obligations of their respective roles. Divorce is understood as the end of marital instability between husband and wife who then live separately and are legally recognized under applicable law. The dynamics of life in the household sphere are increasingly complex, while married couples are required to face these conditions with all the efforts that can be mobilized by both parties. Conflicts that arise from efforts to resolve problems when they are not resolved and resolved will disturb and result in disharmony in the husband-and-wife relationship. As a result of this condition, quarrels often arise which in the end make them feel that their marriage is not as expected and feel disappointed. To overcome this disappointment, husband and wife must negotiate, if the negotiation is successful then the husband-and-wife relationship will improve, on the contrary if the husband and wife do not negotiate then it is possible for the marriage to be destroyed or divorced. The objectives of this community service activity are increased knowledge and understanding of student participants about Divorce on Family Perspective, and good attitude when finished delivering the material. The method used is to provide an understanding of the participants regarding the divorce on family perspective so that participants can apply it in society. After the counseling there was an understanding of the meaning of Divorce on Family Perspective for each participant and increasing the knowledge and understanding of participants at the Faculty of Psychology, Potential Utama University in understanding the material given in the counseling that has been held with the theme Giving Psychoeducation "Divorce on Family Perspective" to Psychology Students at the Potential Utama University.